EXAMINATION OF PROFESSIONAL ETHICS OF INDEPENDENT AUDITORS IN THE LIGHT OF IMMANUEL KANT’S ETHICAL PRINCIPLES - İlkay Ejder ERTURAN (Sayıştay Dergisi, 2025)
Independent auditors assume a great responsibility towards information users with the report they submit at the end of the audit. With this sense of responsibility, the independent auditor must act in accordance with the ethical principles of the profession while performing the audit work. The basic professional ethical principles of independent auditors have been determined as integrity, impartiality, professional competence and care, confidentiality and professional behavior. In the study, the professional ethical principles of independent auditors have been examined in the context of the principles of good will, categorical imperative and freedom that constitute the moral ethical principles of German philosopher Kant. The purpose of this study is to examine the compatibility of Kant’s ethical principles with the ethical principles of today’s independent auditors. In the study, the professional ethics of independent auditors have been examined in the light of Kant’s ethical principles, aiming to provide a perspective to these principles. For this purpose, domestic and foreign literature has been scanned, and the obtained study findings have been tabulated and presented as a result. Kant’s moral ethical principles have been examined in many scientific fields but have not been addressed in the field of auditing. Therefore, this study is significant as it is the first to address these principles in the field of auditing.